Mouse SAMHD1 has antiretroviral activity and suppresses a spontaneous cell-intrinsic antiviral response - Behrendt, Rayk; Schumann, Tina; Gerbaulet, Alexander; Nguyen, Laura A.; Schubert, Nadja; Alexopoulou, Dimitra; Berka, Ursula; Lienenklaus, Stefan; Peschke, Katrin; Gibbert, Kathrin; Wittmann, Sabine; Lindemann, Dirk; et al. (Cell Reports, 2013)
Aicardi-Goutières syndrome (AGS), a hereditary autoimmune disease, clinically and biochemically overlaps with systemic lupus erythematosus (SLE) and, like SLE, is characterized by spontaneous type I interferon (IFN) production. The finding that defects of intracellular nucleases cause AGS led to the concept that intracellular accumulation of nucleic acids triggers inappropriate production of type I IFN and autoimmunity. AGS can also be caused bydefects of SAMHD1, a 3@ exonuclease and deoxynucleotide (dNTP) triphosphohydrolase. Human SAMHD1 is an HIV-1 restriction factor that hydrolyzes dNTPs and decreases their concentrationbelow the levels required for retroviral reverse transcription. We show in gene-targeted mice that also mouse SAMHD1 reduces cellular dNTP concentrations and restricts retroviral replication in lymphocytes, macrophages, and dendritic cells. Importantly, the absence of SAMHD1 triggered IFN-β-dependent transcriptional upregulation of type I IFN-inducible genes in various cell types indicative of spontaneous IFN production. SAMHD1-deficient mice may be instrumental for elucidating the mechanisms that trigger pathogenic type I IFN responses in AGS and SLE
CRIS-Team Scopus Importer:2024-07-25